“Wisdom Seeking Together”: Circling around Research Ethics - Auger, Josie C.; Nath, Nisha; Greene, Carolyn (The International Indigenous Policy Journal, 2023)
Before Indigenous scholars engage in decolonial research with human participants, Canadian universities must grant them ethics approval. Grounded by the experiences of the nehiyaw researcher and the Chair of the research ethics board who reviewed the research, we explore the experience of REB review with research exploring self-determination and sovereignty with nehiyaw iskwewak (Cree females) as Knowledge Holders. In accordance with iyiniwak (Indigenous Peoples) beliefs, the co-creators and authors positioned themselves in the centre of a circle with Natural Law teachings of kindness, honesty, caring, strength, and determination. In this shared space, we brought together dialogues connected to thematics grounded in ceremony, Natural Law (iyiniwak teachings), and cyclical process. Through four directions, we examine colonial processes and identify REB accountabilities.